'Living between Two Lions': Civilian Protection Strategies during Armed Violence in the Eastern Democratic Republic of the Congo. Issue 3 (December 2017) - Suarez, Carla
This article examines how civilians assess, negotiate with, and in some cases deceive armed actors in the eastern Democratic Republic of the Congo (DRC). It demonstrates that civilians not only navigate the precarious and unpredictable conditions within armed conflict, but also exploit these conditions to improve their security situations. The 'self-protection' strategies analysed aim to prevent, mitigate and confront violent threats that civilians encounter in their daily lives. This article argues that civilian self-protection strategies are especially prevalent in contexts marked as 'no peace – no war'. Characterised by prolonged and low intensity violence, 'no peace – no war' contexts shape civilian self-protection strategies in three ways. First, civilians often develop a sophisticated understanding of the actors involved and the patterns of violence that unfold. Second, civilians often learn what particular strategies are most likely to be successful, typically through trial and error. Third, civilians have often become sceptical and cynical about international actors and activities. Understanding what actions civilians take to protect themselves, their families, and their communities is critical for the international community's role in peacemaking and peacebuilding.